Effects of advance care planning on confidence in surrogates' ability to make healthcare decisions consistent with older adults' wishes: Findings from a randomized controlled trial. Issue 7 (July 2018) - Bravo, Gina; Sene, Modou; Arcand, Marcel; Hérault, Élodie
Highlights: Advance care planning (ACP) aims at helping surrogates make decisions for a loved one. We previously reported on an ACP intervention designed for older adults and surrogates. The intervention did not help surrogates predict the older adult's healthcare wishes. Here, we focused on confidence in surrogates' ability to make consistent decisions in the future. Confidence levels improved post-intervention, among both older adults and surrogates. Abstract: Objective: To investigate how confidence in surrogates' ability to make consistent decisions in the future change over time, in the context of an ACP intervention that did not improve surrogates' ability to predict an older adult's hypothetical treatment preferences. Methods: The study involved 235 older adults and surrogates, randomly allocated to an ACP or control intervention. At baseline, end of intervention, and six months later, participants were asked how confident they were in the surrogate making decisions in the future that would match the older adult's wishes. Results: By the end of the intervention, confidence had increased among older adults and surrogates involved in ACP (OR = 3.1 and 5.8 respectively, p  < 0.001), while less change occurred among controls. Over the following six months, confidence remained stable among older adults but decreased among surrogates (OR = 0.5, p  = 0.005). Conclusion: ACP increases confidence in surrogates' ability to make consistent decisions, which may lighten the burden of substitute decision making. Efforts to improve substitute decision-making must continue so that participants' confidence is not based on the mistaken assumption that surrogates can make consistent decisions. Practice implications: Professionals involved in ACP should inform participants that confidence in the surrogate may increase in the absence of enhanced predictive ability.